Defining Satisfactory Methods of Treatment in Rare Diseases When Evaluating Significant Benefit–The EU Regulator's Perspective - Sheean, Maria E.; Naumann-Winter, Frauke; Capovilla, Giuseppe; Kalland, Maria Elisabeth; Malikova, Eva; Mariz, Segundo; Matusevicius, Darius; Nistico, Robert; Schwarzer-Daum, Brigitte; Tsigkos, Stelios; Tzogani, Kyriaki; Larsson, Kristina; et al. (Frontiers in Medicine, 2021)
Since the implementation of the EU Orphan Regulation in 2000, the Committee for Orphan Medicinal Products at the European Medicines Agency has been evaluating the benefits of proposed orphan medicines versus satisfactory treatment methods. This type of evaluation is foreseen in the orphan regulation as the orphan designation criterion called the ‘significant benefit’. In this article, based on 20 years of experience, we provide a commentary explaining what is considered a satisfactory method of treatment in the context of the EU Orphan Regulation and for the purpose of the assessment of significant benefit. We discuss the challenges posed by continuously changing clinical practice which is associated with the increasing number of treatment options, evolving nature of medicinal therapeutic indications and our understanding of them.